THE OVERVIEW OF INTRAOPERATIVE AWARENESS EVENTS IN PATIENTS POST SURGERY WITH GENERAL ANESTHESIA IN THE GENERAL HOSPITAL ARIFIN ACHMAD - FERA WISDARTI (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Intraoperative awareness is a rare complication of general anesthesia but its an unpleasant phenomenon and can continue into Post traumatic stress disorder that can impair the quality of life of patients after the surgery with general anesthesia. The aims of the present study was to determine the incidence of intraoperative awareness events in patients post surgery with general anesthesia in the general hospital arifin achmad of riau province.this is a descriptive study based on questionnaire of brice interview that was carried out in patients after the surgery with the general anesthesia. The interview data obtained from 35 patients.none of them experienced awareness during general anesthesia. Possible awareness observed in 1 patient (2,86%) and 2 patiens (5,72%) experienced dreaming. The incidence of intraoperative awareness in this study was low.Keywords: awareness, post traumatik stress disorder, possible awareness, dreaming.